NESHAKI: KINFOLK AND TRADE - Patterson, E. P. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1990)
A variety of written documents make reference to Neshaki, a Nishga chief who had a successful trading career, challenged other chiefs through feasts and a pole-raising and was a prominent early convert, before her marriage to a retired Hudson’s Bay Factor. The picture of Neshaki that can be drawn out of the written sources is partial and is certainly shaped by the nature of the written records; even at a distance and through such strained focus, it is a portrait of a remarkable woman.